Benzyl 2-(benzylsulfanyl)benzoate - Leka, Zorica (International Union of Crystallography, 2013)
In the title compound, C(21)H(18)O(2)S, the central aromatic ring makes dihedral angles of 5.86 (12) and 72.02 (6)° with the rings of the terminal O-benzyl and S-benzyl groups, respectively. The dihedral angle between the peripheral phenyl rings is 66.16 (6)°. In the crystal, molecules are linked by pairs of C—H⋯O hydrogen bonds, forming inversion dimers. These dimers are linked via C—H⋯π interactions, forming a three-dimensional network.